Experimental Investigation on Thermoelectric Chiller Driven by Solar Cell. (16th June 2014) - Chen, Yen-Lin; Chien, Zi-Jie; Lee, Wen-Shing; Jwo, Ching-Song; Cho, Kun-Ching
Abstract : This paper presents experimental explorations on cooling performance of thermoelectric chillers being driven by solar cells, as well as comparison results to the performance being driven by fixed direct current. Solar energy is clear and limitless and can be collected by solar cells. We use solar cells to drive thermoelectric chillers, where the cold side is connected to the water tank. It is found that 250 mL of water can be cooled from 18.5°C to 13°C, where the corresponding coefficient of performance (COP) is changed between 0.55 and 1.05, when solar insolation is changed between 450 W/m 2 and 1000 W/m 2 . The experimental results demonstrate that the thermoelectric chiller driven by solar cell is feasible and effective for energy saving issues.